Loading presentation...

Present Remotely

Send the link below via email or IM


Present to your audience

Start remote presentation

  • Invited audience members will follow you as you navigate and present
  • People invited to a presentation do not need a Prezi account
  • This link expires 10 minutes after you close the presentation
  • A maximum of 30 users can follow your presentation
  • Learn more about this feature in our knowledge base article

Do you really want to delete this prezi?

Neither you, nor the coeditors you shared it with will be able to recover it again.


Make your likes visible on Facebook?

Connect your Facebook account to Prezi and let your likes appear on your timeline.
You can change this under Settings & Account at any time.

No, thanks

Leyes de los signos, del sandwich y de los exponentes.

No description

Yaremis Gomez

on 21 February 2013

Comments (0)

Please log in to add your comment.

Report abuse

Transcript of Leyes de los signos, del sandwich y de los exponentes.

Yaremis Lucia Gómez Cálculo Integral Leyes de los Signos.
Ley del Sandwich
Leyes de Exponentes. Leyes de los Exponentes Ejemplos de Leyes de Exponentes Yaremis Lucia
Colegio Puerto Aventuras.
Tercero de Bachillerato. Tulum, Quintana Roo, México.
20 de febrero de 2012 Ley del Sandwich Consiste en dividir dos fracciones, hallarle el recíproco
a la segunda y después simplificar de forma normal.
Ejemplo: ((x^9/4)/(9/4))=((x^9/4)/1)/(9/4)
= (4x^9/4)/9 Leyes de los signos -Sumas y Restas: Si los signos son:
1.Iguales: Se suman las cantidades y se pone el signo que aparece.
2.Diferentes: Se restan las cantidades y se pone el
signo del mayor.
-Multiplicaciones y divisiones: Si los signos son:
1.Iguales: el resultado es positivo.
2.Diferentes: el resultado es negativo. 1) x^1 = x
2) (-1)^n= (1 si n es par) o (-1 si n es impar)
3) x^0 = 1
4) x^-1 = 1/x
5) (x^m)(x^n) = x^(m+n)
6) (x^m)/(x^n) = x^(m-n)
7) (x^m)^n = x^(mn)
8) (xy)^n = (x^n)(y^n)
9) (x/y)^n = (x^n)/(y^n)
10) x^-n = 1/x^n
11) x^(m/n)= 1) 6^1 = 6^1
2) *Dado en la diapositiva anterior.
3) 7^0 = 1
4) 4^-1 = 1/4
5) (x^2)(x^3) = x^(2+3) = x^5
6) x^4/x^2 = x^(4-2) = x^2
7) (x^2)^3 = x^(2×3) = x^6
8) (xy)^3 = x^3y^3
9) (x/y)^2 = x^2 / y^2
10) x^-3 = 1/x^3
Full transcript